Effectiveness of the Monofilament Test and Ipswich Touch Test (IpTT) in the Early Detection of Neuropathy Complications in Patients with Type 2 Diabetes Mellitus - Sri Sakinah; Muhammad Tahir; Wahyuni; Nurun Salaman Alhidayat (Journal Of Nursing Practice, 2024)
Backgrounds: Diabetes Mellitus is a condition characterized by high levels of sugar in the blood caused by abnormal insulin production in the body, leading to metabolic disorders that can gradually damage parts or all of the body. Diabetes mellitus can cause serious complications if not properly treated or managed, including neuropathy, which is the most common complication resulting in nerve damage. Neuropathy can be detected early in several ways, including using the monofilament test and Ipswich touch test (IpTT). Purpose: To compare the effectiveness of the monofilament test and Ipswich touch test (IpTT) in the early detection of neuropathy complications in patients with type 2 diabetes mellitus. Method: This study is a quantitative quasi-experiment with a posttest-only control group design. The sample in this study consisted of 32 patients with type 2 diabetes mellitus, divided into 2 groups: 16 respondents who were treated with the monofilament test and 16 respondents who were treated with the Ipswich touch test. Due to the results of the statistical analysis indicating non-normally distributed but homogeneous data, the Mann-Whitney test was used for data analysis. Results: From the results of the tests carried out, a significance value of 0.003 < 0.05 was obtained; this suggests that the Monofilament Test and Ipswich Touch Test (IpTT) are effective in the early detection of neuropathy complications in patients with type 2 diabetes mellitus. However, between the two, the monofilament test was found to be more effective compared to the Ipswich Touch Test, with a mean result of 20.84 > 12.16. Conclusions: Both the monofilament test and Ipswich touch test (IpTT) are effective in the early detection of neuropathy complications in patients with type 2 diabetes mellitus.